Factors affecting willingness to provide buprenorphine treatment. - Netherland, Julie; Botsko, Michael; Egan, James E; Saxon, Andrew J; Cunningham, Chinazo O; Finkelstein, Ruth; Gourevitch, Mark N; Renner, John A; Sohler, Nancy; Sullivan, Lynn E; Weiss, Linda; Fiellin, David A (Journal of substance abuse treatment, 2009)
Buprenorphine is an effective long-term opioid agonist treatment. As the only pharmacological treatment for opioid dependence readily available in office-based settings, buprenorphine may facilitate a historic shift in addiction treatment from treatment facilities to general medical practices. Although many patients have benefited from the availability of buprenorphine in the United States, almost half of current prescribers are addiction specialists suggesting that buprenorphine treatment has not yet fully penetrated general practice settings. We examined factors affecting willingness to offer buprenorphine treatment among physicians with different levels of prescribing experience. Based on their prescribing practices, physicians were classified as experienced, novice, or as a nonprescriber and asked to assess the extent to which a list of factors impacted their prescription of buprenorphine. Several factors affected willingness to prescribe buprenorphine for all physicians: staff training; access to counseling and alternate treatment; visit time; buprenorphine availability; and pain medications concerns. Compared with other physicians, experienced prescribers were less concerned about induction logistics and access to expert consultation, clinical guidelines, and mental health services. They were more concerned with reimbursement. These data provide important insight into physician concerns about buprenorphine and have implications for practice, education, and policy change that may effectively support widespread adoption of buprenorphine.
Keywords: Adult; Buprenorphine; Drug Utilization; Female; Health Care Surveys; HIV Infections; Humans; Male; Narcotic Antagonists; Opioid-Related Disorders; Physicians; Prescriptions; Socioeconomic Factors; Specialization